2018
DOI: 10.1158/1535-7163.mct-18-0097
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Differentiation by Histidine-Rich Glycoprotein/Stanniocalcin-2 Complex Regulates Murine Glioma Growth through Modulation of Antitumor Immunity

Abstract: The plasma-protein histidine-rich glycoprotein (HRG) is implicated in phenotypic switching of tumor-associated macrophages, regulating cytokine production and phagocytotic activity, thereby promoting vessel normalization and antitumor immune responses. To assess the therapeutic effect of HRG gene delivery on CNS tumors, we used adenovirus-encoded HRG to treat mouse intracranial GL261 glioma. Delivery of Ad5-HRG to the tumor site resulted in a significant reduction in glioma growth, associated with increased ve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…APOD has been reported to exhibit tumor suppressive activity in some types of tumors (24). OLR1, STC2, and DKK1 correlate with tumor evolution and immunosuppressive effects (25)(26)(27)(28)(29). TNFRSF19, TNFRSF4, DEFB1, CTLA4, and CTSG were identified as protective genes.…”
Section: Discussionmentioning
confidence: 98%
“…APOD has been reported to exhibit tumor suppressive activity in some types of tumors (24). OLR1, STC2, and DKK1 correlate with tumor evolution and immunosuppressive effects (25)(26)(27)(28)(29). TNFRSF19, TNFRSF4, DEFB1, CTLA4, and CTSG were identified as protective genes.…”
Section: Discussionmentioning
confidence: 98%
“…For example, decreased expression of HRG was observed in advanced lung cancer and is associated with the disease stage (Winiarska et al, 2019). Another study has reported that HRG suppresses glioma growth by modulating antitumor immunity through regulating leukocyte differentiation (Roche et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Stanniocalcin-2 (STC2) was also reported as an interacting partner of HRG on the surface of inflammatory cells in vitro. The colocalization of HRG and STC2 in gliomas may play a role for suppressing glioma growth by modulating tumor inflammation through monocyte infiltration and differentiation (Roche et al, 2018). However, whether the interaction of HRG with STC2 may influence the HRG-CLEC-1A-mediated signaling need to be clarified in the future.…”
Section: Discussionmentioning
confidence: 99%